(untitled) (Journal of the College of Basic Education, 2024)
The goal of the current research is to identify scientific thinking and cognitive curiosity among university students and what is the correlation between them. For the purpose of verifying this, the researcher adopted the scientific thinking scale of (Al-Shammari 2010), which in its final form consists of (46) items, and each item has five alternatives after psychometric characteristics procedures according to the construction methodology. The scale (Mazloum 2016) was adopted, which consists of (30) items in its final form, and the response to the scale consists of four alternatives. After statistical procedures, the psychometric characteristics were calculated for the research sample (400) male and female students from the university who were chosen randomly. After collecting the information and processing it statistically, the researcher reached the following results. : - University students enjoy scientific thinking. - University students have a good level of cognitive curiosity. - There is a positive, significant relationship between scientific thinking and cognitive curiosity. Based on the results of the current research, some future recommendations and proposals were reached.